MODERN APPROACHES TO THE PROCESS OF SOCIALIZATION OF UNIVERSITY STUDENTS - Soldatchenko, Aleksandr; Butova, Anna; Dubskikh, Angelina; Kisel, Olesya (Revista Inclusiones, 2020)
The relevance of the research is determined by the socio-economic situation in modern society. Its specificity is caused by rapid development of information and communication technologies and the introduction of innovative methods in industrial practice. The result is an increase in the number and intensity of social contacts. Thus, the current specialists are required to possess not only professional competence, but also the ability to interact effectively with various social agents in a changing situation, to make responsible decisions, to combine personal and public interests, to execute civil duties and to function as a full-fledged member of society.in other words, be socially mature. The above-mentioned requirements are formulated in the social order presented in key normative documents: federal state educational standards regulating the functioning of the system of higher education. The novelty of the research lies in the development of a continuous- synergetic approach and establishing peculiarities of its realisation to the formation of university undergraduates’ social maturity. As a result, objective laws were revealed, principles were outlined, and the rules for the formation of university undergraduates’ social maturity were formulated from the point of view of the continuous-synergetic approach. The findings can be used to develop pedagogical technologies of its formation. Besides, process peculiarities of the formation of university undergraduates’ social maturity were revealed.